A revision of the Patagonian predaceous midges of the subgenus Acanthohelea of Stilobezzia excluding the S. (A.) edwardsi group (Diptera: Ceratopogonidae) - Cazorla, Carla Gisela (2014)
In this revision of the Patagonian predaceous midges of Stilobezzia (Acanthohelea) (Diptera: Ceratopogonidae), the seven previously known species, Stilobezzia bicinctipes Ingram and Macfie, S. hirsuta I. and M, S. ornaticrus I. and M, S. patagonica I. and M, S. rava I. and M, S. succinea I. and M. and S. varia I. and M. are redescribed, illustrated and their distributions are expanded. Diagnoses are provided for Stilobezzia curvistyla Cazorla and Spinelli, S. longisternalis Cazorla and Spinelli and S. nigerrima I. and M, and the male of S. bicinctipes and the female of S. ornaticrus are described for the first time. Seven new species are described with photographs: S. estepae, S. mapuche, S. megatheca, S. monomorphica, S. pabloi, S. spinosa and S. tridentis. The species are illustrated by photographs, and a key to males and females is provided as well as distributional maps for all species.